2014
DOI: 10.1016/j.nuclphysb.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

ODE/IM correspondence and modified affine Toda field equations

Abstract: We study the two-dimensional affine Toda field equations for affine Lie algebra $\hat{\mathfrak{g}}$ modified by a conformal transformation and the associated linear equations. In the conformal limit, the associated linear problem reduces to a (pseudo-)differential equation. For classical affine Lie algebra $\hat{\mathfrak{g}}$, we obtain a (pseudo-)differential equation corresponding to the Bethe equations for the Langlands dual of the Lie algebra $\mathfrak{g}$, which were found by Dorey et al. in study of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 80 publications
2
37
0
Order By: Relevance
“…Note added -This paper is based on chapters 5 and 6 of [17], submitted by PA for the award of PhD in October 2013. As we were completing the article, we became aware of the preprint [21], which also reports results on the A (1) n massive ODE/IM correspondence and extends the analysis to all simply laced affine Lie algebras and A (2) 2n , D …”
Section: Discussionmentioning
confidence: 99%
“…Note added -This paper is based on chapters 5 and 6 of [17], submitted by PA for the award of PhD in October 2013. As we were completing the article, we became aware of the preprint [21], which also reports results on the A (1) n massive ODE/IM correspondence and extends the analysis to all simply laced affine Lie algebras and A (2) 2n , D …”
Section: Discussionmentioning
confidence: 99%
“…These results were extended to massive Integrable Quantum Field Theories (IQFT) [27] (for recent developments, see also refs. [28][29][30][31][32][33][34][35]). The general relation of this type will be referred to in the paper as the ODE/IQFT correspondence.…”
Section: Jhep01(2018)021mentioning
confidence: 99%
“…This was generalized to a relation between the classical Tzitzéica-Bullough-Dodd equation (A (2) 2 algebra) and the quantum Izergin-Korepin model in [9], and was studied for type A (1) r affine Toda theories in [10,11]. In these works it was shown that connection coefficients for subdominant solutions to the linear problem associated with the affine Toda field equation correspond to the vacuum eigenvalues of Q-operators for g-type quantum integrable models.…”
Section: Introductionmentioning
confidence: 99%
“…In these works it was shown that connection coefficients for subdominant solutions to the linear problem associated with the affine Toda field equation correspond to the vacuum eigenvalues of Q-operators for g-type quantum integrable models. The work of [11] looked at ABCDG-type affine Lie algebras and found that the (pseudo-)ordinary differential equation associated with ĝ ∨ affine Toda field equation was the same as that of [6] for simple Lie algebra g after taking the conformal limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation